Décrypter l’expression linguistique et la représentation textuelle dans les sources du droit - Caroline Laske (Criminocorpus, 2025)
This paper proposes textual representation as a conceptual tool for researching women’s legal capacity by placing language (both the explicit discourse and the encoded meanings) at the centre of the study. The hypothesis is that a major element of the reality of women’s legal capacity lies in the experience of the attitudes/biases women face, which impose constraints on their capacity to act with legal authority. To achieve an all-round understanding of that reality, there is a need to go beyond the normative framework that can be found in the legal/administrative sources and examine these for the linguistic expression used to regulate women’s legal status and their legal capacity to act.